Nonvolatile Reconfigurable Electromagnetically Induced Transparency with Terahertz Chalcogenide Metasurfaces. Issue 4 (20th January 2022) - Liu, Kuan; Chen, Xieyu; Lian, Meng; Jia, Jingyuan; Su, Ying; Ren, Haonan; Zhang, Shoujun; Xu, Yihan; Chen, Jiajia; Tian, Zhen; Cao, Tun
Abstract: Metasurface analog of electromagnetically induced transparency (EIT) provides a compact platform for generating a narrow‐band transmission window with very sharp spectral features. They hold promise for many appealing applications including ultrasensitive detectors, slow‐light devices, nonlinear optical devices etc. In particular, reconfigurable EIT metasurfaces are crucial for expanding the capability of light field control, which are promising for terahertz (THz) communications and optical networks. Yet, the investigation on reconfigurable EIT metasurfaces with nonvolatile operation remains scarce. Here, reversible switching of the metasurface‐induced transparency in the THz spectrum is experimentally realized. The reconfigurable response (reversible spectral shift) is obtained by integrating a nonvolatile chalcogenide phase change material, Ge2 Sb2 Te5 (GST225) into the meta‐atoms. A giant reversible switching of EIT takes place under an excitation of nanosecond laser pulses, showing a reconfigurable group delay of the THz waves. The proposed reconfigurable THz metadevices may provide a new route for the ultrafast laser induced switching and reconfigurable slow‐light devices. Abstract : Reversible switching of the metasurface‐induced transparency in the THz spectrum is experimentally realized. The reconfigurable response is obtained by integrating Ge2 Sb2 Te5 into the meta‐atoms. A giant reversible switching of electromagnetically induced transparency occurs under an excitation of nanosecond laser pulses, showing a reconfigurable group delay of THz waves.